Beyond the Average: Peer Heterogeneity and Intergenerational Transmission of Education - Tanika Chakraborty; Olga Nottmeyer; Simone Schüller; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2014)
Estimating the effect of 'ethnic capital' on human capital investment decisions is complicated by the endogeneity of location choice of immigrants and the reflection problem. We exploit a rare immigrant settlement policy in Germany to identify the causal impact of parental peer-heterogeneity on the educational outcomes of their children. To identify the direction of peer effect we restrict to no-child-adult-peers who completed their education much before the children in our sample of interest. We find that children of low-educated parents benefit significantly from the presence of high-educated neighbors, with more pronounced effects in more polarized neighborhoods and significant gender heterogeneity. In contrast, we do not find any negative influence coming from the low-educated neighbors. Our estimates are robust to a range of flexible peer definitions. Overall, the findings suggest an increase in parental aspirations as the possible mechanism rather than a direct child-to-child peer effect.
Keywords: R23; J15; I21; 330; education; ethnic capital; Germany; immigrant; peer effects; policy experiment